Analysis of neuronal cardiolipin and monolysocardiolipin from biological samples with cyclic ion mobility mass spectrometry - Emaus, Katlynn J.; Dunbar, Carmen A.; Caruso, Joseph; Ruotolo, Brandon T.; Wider, Joseph M.; Sanderson, Thomas H. (Frontiers in Physiology, 2025)
The mitochondrial phospholipid cardiolipin (CL) is essential for proper mitochondrial function and energy production. Cardiolipin has four distinct fatty acid tails with varying expression compositions, resulting in a highly variable tissue-specific distribution of isomer expression. Neuronal cardiolipin has a remarkable variety of subspecies and has recently been used as a biomarker to predict brain injury severity following cardiac arrest and traumatic brain injury. Multiple conditions have been associated with disordered cardiolipin remodeling, including Alzheimer’s disease, Parkinson’s disease, Barth syndrome, and astrocytoma. The clinical relevance of cardiolipin as a biomarker and the importance of the mechanistic role of cardiolipin remodeling in disease emphasize the demand for a reliable and accurate means of the identification and quantification of cardiolipin. In this study, we outline the use of a novel method of cardiolipin analysis using cyclic ion mobility mass spectrometry (cIMS-MS) to isolate and identify cardiolipin subspecies in several biological samples. Furthermore, cIMS-MS established the composition of the cardiolipin profile by individual subspecies across biological samples under basal conditions. Monolysocardiolipin (MLCL), the precursor of mature cardiolipin and a primary diagnostic biomarker of Barth syndrome, was isolated from cardiolipin and identified. The monolysocardiolipin:cardiolipin ratio was quantified in brain samples from tafazzin-knockout (KO) mice, demonstrating accumulation of MLCL and providing direct evidence for the validity of this cIMS-MS methodology through genetic loss-of-function. The novel, multiple-pass feature of cIMS-MS enabled the isolation and amplification of less abundant cardiolipin subspecies in both standards and biological samples. This protocol enables rapid analysis of biological samples, allowing researchers to further dissect the mechanistic role of cardiolipin in injury pathology, with simplified sample preparation and reduced potential for artifact introduction.